Perancangan User Interface (UI) Aplikasi Kuis Anak Usia Dini Berbasis Android dengan Metode User-Centered Design - Alvinus Yodi; Yosefina Finsensia Riti (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2023)
In this research, the primary objective was to design an innovative user interface (UI) for an Android based quiz application targeted at early childhood education. The User-Cantered Design approach served as the foundation for the entire design process, with a focus on gaining an in-depth understanding of user needs, exploring creative ideas, and developing prototypes that meet their expectations. The resulting design incorporates specific elements tailored to support children's learning, including educational quiz games, visually appealing displays, and an intuitive user experience. Through a series of stages, including problem identification, user understanding, persona creation, brainstorming ideas, prototype development, and testing with early childhood users, this research successfully achieved an engaging and interactive UI design. Data from questionnaires indicated that a majority of respondents gave a score of 74 reflecting a positive evaluation of the user interface. This signifies the design's success in enhancing the learning experience of early childhood learners. These findings can serve as a robust foundation for the development of more effective and engaging educational quiz applications for young children, with a focus on an educational and intuitive user experience.